(untitled) (Pulse, 2016)
The cerebral palsies are a group of conditions due to non progressive damage to the brain before, during or after birth. There are many causes. Although the brain damage itself doesnt change nor is it curable, the symptoms may change with time. Classifications vary in different clinics and countries. usually there is the spastic, the athetoid and the ataxic type. The diagnostic classification may not play a direct role in the therapy plans. Diagnostic types are based on the predominant symptoms and there may be symptoms of the other types Although the motor delay and dysfunctions are the main problems in the cerebral palsies there is the possibility of other handicaps. The brain damage itself can be diffuse enough to affect speech and hearing, vision, perceptual function, mental ability and general behaviour. Epilepsy may occur. There may also be other associated handicaps which are due to lack of motor experiences in physically disabled children. Lack of motor exploration affects development of sensation perceptions, mental abilities and speech, emotional and social skills are also hampered. Parent-Child interaction is not always easy and may create emotional problems. Early therapy is advisable to minimize the degree of motor handicap and of the secondary development handicaps. Pulse Vol.8 January-December 2015 p.73-76